Effectiveness of direct-acting antivirals in Hepatitis C virus infection in haemodialysis patients - Soraya Abad (Nefrología (English Edition), 2017)
Hepatitis C virus (HCV) infection is highly prevalent among patients on haemodialysis and leads to a poorer prognosis compared to patients who do not have said infection. Treatment with interferon and ribavirin is poorly tolerated and there are limited data on the experience with new direct-acting antivirals (DAAs). The aim of this study is to retrospectively analyse the current prevalence of HCV infection and efficacy and safety results with different DAA regimens in the haemodialysis population of 2 hospital areas. This is a multicentre, retrospective and observational study in which HCV antibodies were analysed in 465 patients, with positive antibody findings in 54 of them (11.6%). Among these, 29 cases (53.7%) with genotypes 1 and 4 were treated with different DAA regimens, including combinations of paritaprevir/ritonavir, ombitasvir, dasabuvir, sofosbuvir, simeprevir, daclatasvir and ledipasvir, with/without ribavirin. Mean age was 53.3 ± 7.9 years, 72.4% of patients were male and the most important aetiology of chronic kidney disease involved glomerular abnormalities. In 100% of cases, a sustained viral response was achieved after 24 weeks, regardless of DAA regimen received. Adverse effects were not relevant and no case required stopping treatment. In 15 cases, ribavirin was combined with the DAA. In these cases, the most significant adverse effect was anaemic tendency, which was reflected in the increase of the dose of erythropoietin stimulating agents, although none required transfusions. In summary, we conclude that new DAAs for the treatment of HCV in haemodialysis patients are highly effective with minimal adverse effects; it is a very important advance in HCV management. These patients are therefore expected to have a much better prognosis than they have had until very recently.